Analysis of Suggestions on Corporate Income Tax Planning - Cheng, Xiaojun (Journal of Theory and Practice of Management Science, 2023)
In the process of daily operation and development, enterprises will involve many types of taxes. Among them, enterprise income tax is the most basic and key tax, enterprise leaders and decision makers should do a good job of tax planning, in the case of law, reduce taxes, save costs. This paper focuses on the tax planning of the enterprise income tax, aiming at promoting the stable development of enterprises. Enterprises need to understand the control policies of tax authorities, especially the trend of digital tax administration. For example, the introduction of the fourth phase of the Golden tax system has made the tax authorities' supervision of enterprises more comprehensive. In addition, enterprises also need to pay attention to the impact of digital tax management. For example, the enterprise information network verification system involving banks and non-bank payment institutions can timely verify the mobile phone real name information, enterprise tax status, enterprise registration information and other important information, so as to prevent enterprise account opening risks and reduce the work burden of financial personnel.